Pendampingan Penghitungan Harga Pokok Produksi Umkm Pelangi Bakery Berbasis Aktivity Based Costing - Agustiawan Agustiawan; Linda Hetri Suriyanti; Wira Ramashar; siti samsiah; nadia fathurrahmi lawita; Dwi Fiona Sari (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Businesses that want to continue to survive in the era of the Asian Economic Community must have the right decisions in determining production costs. Calculation of production costs has an important role in manufacturing companies because it will affect the selling price and can provide optimal profits for the company. Determination of the cost of goods manufactured is very important in the company as a basis for determining the cost of goods sold, so that it can compete with other companies. Activity Based Costing (ABC) system is a production cost calculation system based on the activities consumed by each product. The calculation of the cost of production at the Pelangi Bakery still uses manual calculations or the traditional system. Determination of the cost of production using the ABC system at the Sumber Rejeki bakery has not been able to determine the cost of production correctly because there are several obstacles. The result of calculating the cost of production per unit of the ABC system is greater than the traditional system.